Mathematical Modelling of the Geographic Spread of Rabies Epidemic - Nur Hayatulfarah, Roslan (Universiti Malaysia Sarawak (UNIMAS), 2019)
Zoonotic disease is infectious disease of animals that can cause diseases when transmitted to human. Rabies is a deadly disease that can be spread through bite or scratch or through contact with saliva from the infected animal. Since 1884, rabies has been known to occur in Malaysia. Recent outbreak was occurred in Sarawak started July 2017 with 21 deaths cases recorded. In order to investigate the immigration of dog affects the geographically spread of rabies in Sarawak, mathematical patchy model is used to describe the transmission dynamic of rabies between dogs and human. In each patch the submodel consists of susceptible, vaccinated, exposed and infected subpopulation of both dog and human (SEIV model). Mathematical modelling was proposed to provide a scientific basic for public health authorities in Malaysia and particularly in Sarawak to reduce and prevent the geographic spread of rabies. The control measure includes the vaccinating the dogs, culling stray dogs and transportation of dogs need to be monitored and under constant surveillance.